The formulation of classification for Islamization in medicine: review on 15 Years of publications from Kulliyyah of Medicine - Shahar, Mohammad Arif; Idris, Mohd Faiz; Che Mohamad, Che Anuar; Razali, Zul Azlin (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Background: The Kulliyyah of Medicine of IIUM has pioneered the Islamization of Medicine in Malaysia since its establishment in year 1994. Therefore, it is timely to review publications on Islamization by the kulliyyah and also to propose a classification system in the field of researches to promote an organized, comprehensive, inclusive and relevant Islamization process.